Etika Yoga Dalam Kitab Siva Samhita - I Made Adi Brahman; I Gusti Made Widya Sena (Jurnal Yoga dan Kesehatan, 2023)
The Siva Samhita or collection of Siva's teachings is a yoga text that describes the teachings of yoga in a complete and in-depth manner. One of the components of yoga described in the text is the ethical teachings that must be carried out by yoga practitioners who want to achieve success in yoga. This study provides theoretical support and enriches the body of knowledge about yoga ethics. This research is classified as a qualitative research with Siva Samhita as the object of study. The data were analyzed by the following steps: data reduction, data classification, data display, interpretation and conclusion. The results of this study include: 1) When carrying out dhyana yoga (meditation) you should always pray homage to Guru and Lord Ganesha as opening the way to success. 2) All kinds of food and actions that do not support progress in yoga are to be avoided. Vice versa, all kinds of food and actions that support the progress of yoga should be done with full discipline and without attachment. 3) Enjoyment (bhoga) engendered by the five senses should be avoided as they only serve as a hindrance to progress in yoga.